What is misophonia and how can we treat it?. (April 2014) - Cavanna, Andrea E
<x xml:space="preserve">Abstract</x> Selective sound sensitivity syndrome or misophonia is a chronic condition characterized by unpleasant emotional experiences and autonomic arousal in response to specific sounds. Over the last few years there have been a few reports detailing the clinical features associated with this condition. These focused reports raise interesting questions about the nosological status of this potentially disabling clinical entity.